Patriotisme Sufistik Ibn al-Taymīyah; Konsep dan Kiprahnya - Moch. Kalam Mollah (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2020)
This paper examines the thoughts of a famous Muslim figure named Ibn al-Taymīyah. As an individual who lives in an era of heterogeneous society and full of political upheaval, the figure born in al-Harrān has ideas that are arguably unique and different from his predecessors. By examining relevant literature sources, the writer finds that Ibn al-Taymīyah's ideas differ from the majority of pre-existing thoughts. For him, a leader must have the skills, skills and a sense of justice in leading the country. In addition, he is also known as a patriot who has dedicated himself to the interests of the nation and state. Apart from being an intellectual as well as a patriot with a spirit of state solidarity, Ibn al-Taymīyah was also known as one who had such a strong Sufistic conception. This concept emphasizes that the motivation to defend the nation and state must be balanced with zuhud and sincerity that humans are part of a human entity that cannot be separated from the theological aspect.